The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21203/rs.3.rs-292930/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Initial Study on TMPRSS2 p.Val160Met Genetic Variant in COVID-19 patients

Abstract: BackgroundCoronavirus disease 2019 (COVID-19) is a global health problem that causes millions of deaths worldwide. The clinical manifestation of COVID-19 widely varies from asymptomatic infection to severe pneumonia and systemic inflammatory disease. It is thought that host genetic variability may affect the host's response to the virus infection and thus cause severity of the disease. The SARS-CoV-2 virus requires interaction with its receptor complex in the host cells before infection. The transmembrane prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 25 publications
(35 reference statements)
1
19
0
Order By: Relevance
“…To date, various in silico analyses have been made using different bioinformatics tools to identify and predict TMPRSS2 gene host polymorphism against SARS-CoV-2. As our results show, a study by [48] has shown that the TMPRSS2 p. Val160Met polymorphism was associated with SARS-CoV-2 infectivity. A recent investigation by Asselta et al reported the existence of some TMPRSS2 polymorphisms, namely, rs2070788, rs9974589, and rs7364083.…”
Section: Discussionsupporting
confidence: 76%
“…To date, various in silico analyses have been made using different bioinformatics tools to identify and predict TMPRSS2 gene host polymorphism against SARS-CoV-2. As our results show, a study by [48] has shown that the TMPRSS2 p. Val160Met polymorphism was associated with SARS-CoV-2 infectivity. A recent investigation by Asselta et al reported the existence of some TMPRSS2 polymorphisms, namely, rs2070788, rs9974589, and rs7364083.…”
Section: Discussionsupporting
confidence: 76%
“…Of these, eight studies were pooled to explore associations of genetic polymorphisms with COVID-19 severity. 13,14,20,[36][37][38][39][40][41][42][43] After scrutinising all eligible studies, we summarised and classified major events associated with polymorphisms by focussing on host genetic variants: ACE1 rs1799752, ACE1 rs4646994, ACE2 rs2285666, and TMPRSS2 rs12329760. Descriptive data of the included studies are demonstrated in Table 1.…”
Section: Systematic Searchmentioning
confidence: 99%
“…For the disease severity, eight out of 11 studies providing data on genetic distributions of ACE1 rs4646994, 13,14,37,38 ACE2 rs2285666, 13,37,40 and TMPRSS2 rs12329760 [41][42][43] in non-severe and severe COVID-19 patients were selected for meta-analyses. All meta-analyses unveiled that three genetic polymorphisms of ACE1 rs4646994, ACE2 rs2285666, and TMPRSS2 rs12329760 were significantly associated with a higher risk of developing severe Subsequent meta-analysis demonstrated significant associations between ACE2 rs2285666 polymorphism and an increased risk of developing severe COVID-19 in two genetic models (recessive GG vs. GA + AA, OR = 2.14, 95% CI: 1.26, 3.66, p = 0.005, I 2 = 21%; additive GG vs. GA, OR = 2.14, 95% CI: 1.14, 4.01, p = 0.02, I 2 = 0%), as illustrated in Figure 3c,d.…”
Section: Disease Severity Of Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exploring the role of the in ammasomes in the SARS-CoV-2 infection is still needed due to the recent onset of this pathogen. Genetic factors contributing to the outcome of SARS-CoV-2 infection are still little known; recently, variants in the speci c sites of the ACE2 and TMPRSS2 genes, as well as the ABO locus and fewer others gene targets were considered as genetic risk factors for COVID-19 outcomes (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%